Assessment of Safety and Operational Standards of Suramadu–Bangkalan Road Using Star Rating: Road Characteristics Identification - Hartatik, Nurani; Muttaqin, Alfian Febriansyah; Punarta, I Gede Agus (Civil and Sustainable Urban Engineering, 2025)
The Suramadu National Road is a strategic corridor connecting Madura Island with the Surabaya metropolitan area, playing a crucial role in supporting public mobility and logistics distribution. The high traffic intensity and vital function of this road section require compliance with safety and roadworthiness standards. However, initial observations indicated several issues, such as malfunctioning street lighting, unauthorized U-turns, and the presence of hazardous objects on the roadside, which could potentially increase the risk of accidents. This highlighted the need for a Roadworthiness Test (ULFJ) evaluation to ensure that this road section met technical and operational requirements. This study aimed to analyze the roadworthiness level of the Suramadu–Bangkalan National Road (Sta 0+100 to Sta 3+400), a 3,392-meter section. The star rating approach, as stipulated in Minister of Public Works and Public Housing Regulation No. 4 of 2023 and Circular Letter 11/SE/Db/2024, was used. Data were obtained through field surveys at 100-meter intervals across 68 assessment segments. The assessment resulted in a Star Rating Score of 10.71, corresponding to a 3-star rating. According to PUPR Ministerial Regulation No. 4 of 2023, the road still met operational requirements and was classified as a safe road based on Circular Letter 11/SE/Db/2024. However, the 3-star rating indicated that several safety aspects only met minimum standards. Therefore, the prepared technical recommendations need to be implemented immediately to upgrade this road section to a safer category with a target rating of 4 or 5 stars.